THE The Influence of Head of Field Leadership on Employee Performance at TRANTIBUM SATPOLPP Bandung City: Pengaruh Kepemimpinan Kepala Bidang Terhadap Kinerja Pegawai Pada TRANTIBUM SATPOLPP Kota Bandung - Fitra Nurhakim; Yunita Fourina Dewi; Handani Binangun (STIA Bagasasi, 2022)
In the era of globalization, every organization or company in the form of private or government, of course, has both short-term and long-term goals to be achieved through the activities it undertakes. In an organization or company, leadership is an important factor. In carrying out its duties, the Public Order and Community Peace Sector, the Civil Service Police Unit of the City of Bandung becomes the spearhead in the implementation of Enforcement of Regional Regulations. because in this field it is more in direct contact with the community and regional regulation violators. The leadership factor on employee performance is needed, so that the quality of employee performance continues to improve, of course this is done with good leadership. The purpose of this study was to determine the impact of leadership carried out by the Head of Public Order and Public Peace of the Civil Service Police Unit in Bandung City. The data were collected using interviews and questionnaires, analyzed using descriptive and regression techniques. While the program used to manage data uses SPSS(Statistics Program for Social Science) version 23. From the results of this analysis, it can be seen that the leadership carried out by the Head of Public Order and Public Peace of the Civil Service Police Unit of the City of Bandung has gone well, the recapitulation results show that leadership is measured based on the elements of leadership amounting to 4,228 or 72.89%. This is included in the high category. Meanwhile, employee performance is measured based on employee performance dimensions of 2,931 or 72.19%. This is included in the high category. Based on these results, it can be said that the performance of employees in the field of Public Order and Public Peace of the Bandung Civil Service Police Unit is quite positive.